The INTEGRATION OF MINERAL OIL AND WATER-WASHING AS AN EFFECTIVE TOOL FOR CONTROL OF PSEUDAULAULACASPIS PENTAGONA (HEMIPTERA: DIASPIDIDAE): INTEGRATION OF MINERAL OIL AND WATER-WASHING - Jafari, Masoud; Damavandian, MohammadReza; Amiri Besheli, Behnam (Journal of Agricultural Sciences (Belgrade), 2025)
The white peach scale, Pseudaulacaspis pentagona Targioni-Tozzetti is one of the most important pests of peach trees in the northern provinces of Iran, especially Mazandaran. The insecticide resistance of P. pentagona female adults has caused that the application of conventional insecticides cannot control this pest, therefore, considering the severe and widespread damage of P. pentagona, it seems necessary to find a suitable alternative for these compounds. This study was aimed to evaluate the efficiency of winter control by water-washing+mineral oil compared to repeated use of insecticides in controlling this pest in peach orchards of Mazandaran province. This experiment was conducted as a completely randomized design with three treatments and five replications in a peach orchard located in Makran village, Miandorud city. 1) Chlorpyrifos (Chlorpyrifos-methyl Kavosh®, 40% EC) and Ethion (Ethion Kavosh®, 47% EC) at a concentration of 2 L/1000L of water, (2) water-washing + mineral oil (Volk Kavosh®, 90% EC) at a ratio of 5% (V/V), and (3) control (no sprayed).  The results of the present study showed that in most of the studied dates, there was a significant difference between the efficiency of water-washing+mineral oil compared to the chemical insecticides in controlling the population of different developmental stages of P. pentagona. In spring, water-washing+mineral oil spraying showed an efficacy of 80.25 and 75.71% in controlling the population of nymphs and the adult of P. pentagona, respectively. In summer, the efficiency of water-washing+mineral oil in reducing the population of nymphs and female adults was 77.00 and 69.12%, respectively. In autumn, water-washing+mineral oil recorded an 70.32 and 71.09% in controlling the populations of nymphs and adult of this pest. While efficiency of the insecticides used on the nymphs and adult was 63.70 and 55.78% in spring, 61.68 and 49.78% in summer, and 37.03 and 40.83% in autumn, respectively. As a result, the findings of the present study showed that winter control by only one time of water-washing+mineral oil had higher and significant efficiency compared to the use of chemical insecticides in three time.
Keywords: white peach scale, mineral oil, chemical insecticide, efficiency